Bernhard Glaeser. Housing, Sustainable Development and the Rural Poor. A Case Study of Tamil Nadu. New Delhi: Sage Publications, 1989. 432 Pages. Hardbound, Indian Rs 465.00. (The Pakistan Development Review, 1997)
Shelter is the most pressing need of the present times. Strategies to satisfy this need are urgently needed, particularly for the rural poor. Since eighty percent of the Indian population lives in the rural areas, the author tries to identify their demand for better houses and the required improvements in construction technology in rural India. This study is the result of a joint project of two institutes, i.e., Indian Institute of Technology (IIT) and Wissenschaftszentrum Berlin für Sozialforschung (Social Science Research Centre, Berlin) (WZB), based on a survey conducted in Tamil Nadu, India. The majority of the rural population covered by this study are landless labourers. The survey covered 300 households in 20 selected villages where 71 percent of the respondents were living in traditional katcha houses made of mud, bamboo, and palm leaves. The study concentrates on the poorest strata of rural society and collects information about socioeconomic properties such as income, occupation, education, energy, and water sources used by the respondents. The respondents were asked during the survey to reveal the household preferences for more living space, privacy, ownership, and availability of public services like piped water, electricity, sewerage system, etc. The analysis is based on 291 (out of 300) questionnaires (households schedule).